Causas e consequências do divórcio em Malanje - Angola ("Temas Sociais" Journal, 2024)
Divorce is, essentialy, the dissolution of marriage, driven by various causes and which produces numerous effects on other social fringes. This article seeks to understand the causes and consequences of the divorce in Malanje. The article is mixed in nature, based on documentar research, using reports from the Malanje Provincial Court and the Malanje Civil Registry Office. The data presented here are approached in a diachronic dimension, pointing out the evolution of marriages celebrated and divorces requested, that is, those dissented and those not dissented between 2016 and 2023. Accordingly, to explain the phenomenon highlighted, we used the Merton is middlerange functionalist theory. It allowed us to explain, fundamentally, the construction of marriage taking into account the social roles played by the spouses in the ralationship, as merriage is considered a social institution where the processo f primary socialization occurs. For this theoretical perspective, this institution can, to a certain extente, become functional or dysfunctional. Thus, divorce arises from marriage as a dysfunctonal resulting from the disarticulation of the concepts of the concepts of manifest and latent function. The article also portrayes infidelity as the main cause of divorce ond avoidance of parenthood as one of the many effects that exist, which would ferer to the concept of perverse effects of Budon is actions.